Enhanced magnetic and room temperature intrinsic magnetodielectric effect in Mn modified Ba2Mg2Fe12O22 Y-type hexaferrite. (27th December 2019) - Abdullah, Md F; Pal, P; Chandrakanta, K; Jena, R; Devi, S; Yadav, C S; Singh, A K
Abstract: We have reported a systematic investigation on structural, magnetic, magnetodielectric and magnetoimpedance characteristics of Y-type Ba2 Mg2 (Fe1− x Mn x )12 O22 (0 ⩽ x ⩽ 0.12) hexaferrite synthesized by solid-state reaction route. Rietveld refinement of x-ray diffraction pattern confirms the phase purity of all the samples with rhombohedral crystal structure. The Mn dopant modulates not only superexchange angle near to the boundary of magnetic blocks but also magnetic transition temperature. Temperature-dependent magnetization data suggests that due to Mn doping at Fe sites, ferrimagnetic to proper screw transition temperature ( T II ) increases from 190 K to 208 K, while there is a decrease in proper screw to longitudinal conical spin transition temperature ( T I ) from 35 K to 25 K. We observe remarkable decrease in the magnetic field from 20 kOe to 12 kOe to produce intermediate spin ordering from ferrimagnetic ordering which can be understood because of modification of superexchange angle due to Mn doping. The value of loss tangent decreases with increasing doping concentration at 300K, i.e. 60% and 180% in BMFM4 ( x = 0.04) and BMFM8 ( x = 0.08) respectively as compared to BMF, suggesting the evolution of intrinsic feature in the doped samples. Magnetodielectric (MD) effect shows that in the low-frequency regime, the robust MD effect is because of Maxwell–Wagner interfacial polarization, whereas in the high-frequency regime intrinsic effect dominates. Further, magnetoimpedance measurement confirms the presence of substantial intrinsic MD% ( 6%) at 1.3 T applied field at 300 K for 4% Mn-doped sample. Finally, the nature and strength of magnetoelectric coupling in BMFM4 and BMFM8 samples at 300 K is found to be biquadratic ( P 2 M 2 ) and maximum strength of coupling is 3.09 × 10 −4 emu 2 g −2 and 2.34 × 10 −4 emu 2 g −2, respectively.